2015
DOI: 10.1186/s40200-015-0188-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laparoscopic gastric plication (LGP) in patients with type 2 diabetes, one year follow-up

Abstract: BackgroundObesity is a major risk factor for the development of type 2 diabetes mellitus. Surgery is one of the most effective treatments for morbid obesity. In a prospective cohort study, we examined the effects of Laparoscopic Gastric Plication (LGP) as a new restrictive technique on remission of type 2 diabetes mellitus.MethodsDuring six years of study from June 2007 through December 2013, 62 patients who underwent bariatric surgery were recruited for our study to determine the effects of weight loss. Sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…In summary, the present study demonstrated the efficacy of LGCP not only as a bariatric procedure but as a metabolic surgery for patient with type II DM as other authors have demonstrated [28,29]. These findings substantiate the preliminary observations by Bradnova et al [8] who studied the short-term metabolic effect of LGCP in diabetic patients.…”
Section: Discussionsupporting
confidence: 91%
“…In summary, the present study demonstrated the efficacy of LGCP not only as a bariatric procedure but as a metabolic surgery for patient with type II DM as other authors have demonstrated [28,29]. These findings substantiate the preliminary observations by Bradnova et al [8] who studied the short-term metabolic effect of LGCP in diabetic patients.…”
Section: Discussionsupporting
confidence: 91%
“…Their findings correspond with those of the 2012 study of Talebpour et al of 800 LGCP patients who, at 5year follow-up, achieved 55.0% EWL (28.0-100.0%) [184]. In a 2015 report by Talebpour et al in 60 LGCP patients who had achieved a maximum weight loss of 57 kg at 6 months, 95.0% of T2DM patients attained resolution at 1 year follow-up, and 2/55 patients who experienced weight regain also regained their T2DM [187]. In the Dolezalova et al study, 58 patients (27.4%) had T2DM at baseline; at 5 years, 65.5% of T2DM was resolved.…”
Section: Indications/contraindications Weight Loss Diabetes Resolutionmentioning
confidence: 98%
“…The underlying mechanisms leading to T2DM improvement/remission following more complex bariatric procedures such as the BPD are not fully clarified yet and appear to involve changes not only in insulin resistance but also in insulin and incretin secretion [ 4 , 5 ]. Novel bariatric procedures such as the laparoscopic gastric plication (P), also referred to as laparoscopic greater curvature plication, total gastric vertical plication, or gastric imbrication [ 5 , 6 , 7 , 8 ], recently has broadened the arsenal of metabolic surgery interventions for the treatment of obese T2DM patients. This newer procedure eliminates the greater gastric curvature and forms a gastric tube by laparoscopic plication/infolding of the greater gastric curvature through placement of one or two rows of non-absorbable sutures or staples, thus reducing the stomach volume and leading to a restrictive effect without utilizing implantable devices (e.g., gastric band), gastrectomy, or intestinal bypass.…”
Section: Introductionmentioning
confidence: 99%